An agent-based model for fuel and CO2 emission costs in multi-modal last-mile logistics - Huskisson, Dominic (Stellenbosch : Stellenbosch University, 2025)
Huskisson, D. 2025. An agent-based model for fuel and CO2 emission costs in multi-modal last-mile logistics. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/89adb462-000a-4d56-b29a-4dc5485cc601